A Educação e a memória do humano. A configuração de um espaço comunitário e identitário de investigação - Azevedo, Stella Zita de (Trabalhos de Antropologia e Etnologia, 2020)
Going beyond the idea that Bioethics is just an epistemic cut of knowledge, we propose a reflection centered on the inseparability of the bioethical problems of fundamental anthropological problems. We reject the reduction of bioethics to the place of crossroads of logocratic paradigms. This article reports a case study when, in the context of a School Grouping of the county of Gondomar, the desire to observe the bioethical dimension in the human development experience, within a horizon of "profane narrativity" (Correia, 2011). It has become imperative to understand the impact of the structuring and formation of bioethical awareness in the way in which the students in question have prospected the bioethical principles and values, included in the curricula of Philosophy. The emphasis that the management of curricula in secondary education gives to biotechnology models in the education and education of young people is criticized, by not incorporating the necessary reflection on the ethical and moral issues that have arisen with the advancement and evelopment of biomedicine, bio-technology and bioengineering, in particular. Starting from the critique of the biotechnological and humanist discourses of modernity, related to the foundations of Bioethics, it is argued that unlike the dominant thought, there is no place for Bioethics as an epistemologically autonomous discipline. The formation and structuring of bioethical consciousness in the educational context involve analyzing the contemporary challenges of its teaching. The overcoming of theoretical and casuistic teaching strategies should be done according to the configuration of a community knowledge space of research, of relations that explain and argue the construction of subjectivities that are interrelated in the exercise of knowledge and understanding of bioethical dilemmatic scenarios that allow us to narrate and to narrate ourselves. In the research developed, most students constructed judgments based on ethical- relational values and bioethical principles, where practical application and proairesis predict ethical-social relationship and dialogue. Proairesis is a shared and communally rational autonomy. Linguistics expressed in the shuttle of speech of this communal understanding, is a condition of a meaningful existence starting from the conception of narrative discourse as an interaction of subjectivities, where epistemology, ethics and politics are implicated.